Desain Sistem Layanan Harga Hasil Pertanian Dan Kehutanan Berbasis SMS Dengan Menggunakan Metode Autoresponse - Imam Asrowardi; Bastaman Syah; Sarono Sarono (Jurnal Ilmiah ESAI, 2008)
Mushrooming SMS-based application has evoked an idea to create an information service on prices of agricultural and forestry products which is accessible through SMS. The objective of this research is to create a design of the SMS-based service system on prices of agricultural and forestry products. The design was made in order that the users can obtain the information quickly, easily, anytime, and anywhere. The method administered in this research was SDLC (System Design Live cycle). The Experiments were conducted by using Simpati, Mentari, ProXL, As, and IM3 as gateway SMS cards. Through these experiments, the system which is capable of sending price information quickly, easily, anytime, and anywhere with 0%sending failure was invented.Â  Â  Keywords : Design, SMS, System.